FENOMENUL "BULLYING" ÎN GRUPUL DE ADOLESCENŢI: PROCES ŞI ROLURI PARTICIPATIVE - USM ADMIN (Moldova State University, 2008)
The paper describes the view of bullying as a social phenomenon, a group process which is largely enabled and maintained by members of a school class. Adolescents are involved in bullying in different ways. Some participant roles taken by individual adolescents in the bullying process were analyzed. Roles assigned to the subjects were Victim, Billy, Reinforcer of the bully, Assistant of the bully, Defender of the victim and Outsider.